Transnasal Brain Sampling for Human Rabies Diagnosis - Moses Barima Djimatey; Abdul-Rahim Abubakar; Augustina Angelina Sylverken; Theophilus Odoom; Braimah Baba Abubakari; John Akwasi Ohemeng; Gowri Yale; Frederic Lohr; Luke Gamble; Anita Mahadevan (Anatomia)
Introduction: Rabies remains a significant global threat, yet accurate estimations of its impact are hindered by the lack of confirmatory diagnoses. Postmortem diagnosis of rabies traditionally involves invasive brain tissue testing, a process met with resistance from deceased patients’ families, impeding consent. This paper presents and evaluates an innovative yet unpublished transnasal approach for postmortem brain tissue collection, offering a minimally invasive, easier, faster, and safer method. This method preserves the cadaver’s integrity, potentially easing family reluctance towards autopsies. The limited testing of both human and animal rabies in Ghana highlights the challenges in diagnosing this fatal disease. Scarce diagnostic resources and the complexity of obtaining brain tissue samples exacerbate the issue. Cultural and religious beliefs surrounding autopsies contribute to familial hesitation, as families view these procedures as disruptive and disfiguring, further complicating consent. Methodology: The transnasal technique involves approaching the brain tissue through the nostrils and cribriform plate without any superficial manipulation of the patient’s head and face, thereby preserving the aesthetics and natural features of the person. Results: Technological advancements and seamless One Health collaboration among governmental, non-governmental, and research entities locally and globally have culminated in Ghana’s first confirmed rabies diagnosis using this method of brain tissue collection. This success emphasizes the efficiency and feasibility of the transnasal brain collection approach and the invaluable role of the One Health approach and collaborative efforts in overcoming diagnostic challenges in rabies control.